Spark plasma sintering of MWCNT reinforced aluminum matrix composites - Lim, Bingxiang. (2009)
Aluminum (Al)/multi-walled carbon nanotubes (MWCNTs) composites with 0.5 wt%, 1.0 wt% and 2.0 wt% were fabricated by spark plasma sintering. The carbon nanotubes were well dispersed using “can rolling” method. MWCNTs were chemically treated with sodium dedecyl sulphate (SDS) for better dispersion by decreasing the inter van- Der walls forces of attraction. The effect of sintering time on the physical and mechanical properties of the Al-MWCNT composites is investigated through laboratory instrumented tests. X-ray diffraction was used to analysis the composites structure. The effects of carbon nanotubes on the mechanical properties of the composite were investigated. Experimental results shows that increasing amount of carbon nanotubes enhance the mechanical properties of the composite. The maximum increment in yield strength and Young’s modulus, compared with pure aluminum matrix were found to be 50% and 65.8% respectively when 2.0 wt% of MWCNTs were added.